Antibiotics in pregnancy influence nasal microbiome and respiratory morbidity in infancy - Céline Rüttimann; Annika Nissen-Kratzert; Nadja Mostacci; Noëmi Künstle; Andrea Marten; Amanda Gisler; Katharina Bacher; Sophie Yammine; Ruth Steinberg; Sven Schulzke; Martin Röösli; Philipp Latzin; et al. (ERJ Open Research, 2023)
Background The effects of prenatal antibiotic exposure on respiratory morbidity in infancy and the involved mechanisms are still poorly understood. We aimed to examine whether prenatal antibiotic exposure in the third trimester is associated with nasal microbiome and respiratory morbidity in infancy and at school age, and whether this association with respiratory morbidity is mediated by the nasal microbiome. Methods We performed 16S ribosomal RNA gene sequencing (regions V3–V4) on nasal swabs obtained from 296 healthy term infants from the prospective Basel–Bern birth cohort (BILD) at age 4–6 weeks. Information about antibiotic exposure was derived from birth records and standardised interviews. Respiratory symptoms were assessed by weekly telephone interviews in the first year of life and a clinical visit at age 6 years. Structural equation modelling was used to test direct and indirect associations accounting for known risk factors. Results α-Diversity indices were lower in infants with antibiotic exposure compared to nonexposed infants (e.g. Shannon index p-value 0.006). Prenatal antibiotic exposure was also associated with a higher risk of any, as well as severe, respiratory symptoms in the first year of life (risk ratio 1.38, 95% CI 1.03–1.84; adjusted p-value (padj)=0.032 and risk ratio 1.75, 95% CI 1.02–2.97; padj=0.041, respectively), but not with wheeze or atopy in childhood. However, we found no indirect mediating effect of nasal microbiome explaining these clinical symptoms. Conclusion Prenatal antibiotic exposure was associated with lower diversity of nasal microbiome in infancy and, independently of microbiome, with respiratory morbidity in infancy, but not with symptoms later in life.